TEACHING ENGLISH AS A SECOND LANGUAGE BY USING INTERACTIVE METHODS - Ashirmatova, Khumora Furkatovna (INTERNATIONAL CONFERENCES, 2023)
This article is about teaching English by using interactive methods. In this article it is considered a lot of interactive methods, especially the importance of using TPR method in teaching English as Second Language.